Blood Coagulation Response and Bacterial Adhesion to Biomimetic Polyurethane Biomaterials Prepared with Surface Texturing and Nitric Oxide Release - Xu, Li-Chong (Acta Biomater, 2018)
A dual functional polyurethane (PU) film that mimics aspects of blood vessel inner surfaces by combining surface texturing and nitric oxide (NO) release was fabricated through a soft lithography two-stage replication process. The fabrication of submicron textures on the polymer surface was followed by solvent impregnation with the NO donor, S-nitroso-N-acetylpenicillamine (SNAP). An in vitro plasma coagulation assay showed that the biomimetic surface significantly increased the plasma coagulation time and also exhibited reduced platelet adhesion and activation, thereby reducing the risk of blood coagulation and thrombosis. A contact activation assay for coagulation factor XII (FXII) demonstrated that both NO release and surface texturing also reduced FXII contact activation, which contributes to the inhibition of plasma coagulation. The biomimetic surface was also evaluated for bacterial adhesion in plasma and results demonstrate that this combined strategy enables a synergistic effect to reduce bacterial adhesion of Staphylococcus epidermidis, Staphylococcus aureus, and Pseudomonas aeruginosa microorganisms. The results strongly suggest that the biomimetic modification with surface texturing and NO release provides an effective approach to improve the biocompatibility of polymeric materials in combating thrombosis and microbial infection.